2001
DOI: 10.1292/jvms.63.389
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Carbon Monoxide-Induced Relaxation in the Guinea Pig Ileal Smooth Muscle.

Abstract: The mechanism of carbon monoxide (CO)-induced relaxation were investigated in the guinea-pig ileum. CO (10%) inhibited the 40 mM KCl-induced contraction. This effect was antagonized by ODQ (1 microM), a soluble guanylate cyclase inhibitor. In contrast, CO did not inhibit the 40 mM KCl-induced increase in cytosolic Ca2+ level ([Ca2+]i). Cumulative addition of KCl induced a graded increase in both [Ca2+]i and muscle tension. In the presence of CO, the increase in muscle tension was attenuated whereas the increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 23 publications
0
1
1
Order By: Relevance
“…The present studies suggest that CO can, in fact, activate the nNOS/NO/ cGMP pathway, confirming that at low concentrations, CO is as an agonist of NO production. This is in contrast to a previously reported study in another species that suggested that CO had little effect on peak I Ba in guinea pig ileal muscle (22). However, a much higher concentration of CO was used, which may have inhibited NO production.…”
Section: Discussioncontrasting
confidence: 76%
“…The present studies suggest that CO can, in fact, activate the nNOS/NO/ cGMP pathway, confirming that at low concentrations, CO is as an agonist of NO production. This is in contrast to a previously reported study in another species that suggested that CO had little effect on peak I Ba in guinea pig ileal muscle (22). However, a much higher concentration of CO was used, which may have inhibited NO production.…”
Section: Discussioncontrasting
confidence: 76%
“…The effect of CO on voltage-dependent calcium channels in guinea pig ileum smooth muscle cells was directly studied using the whole-cell patch clamp technique. CO (100 M) had little effect on the peak Ba 2ϩ currents (I Ba ) when voltage was stepped from Ϫ60 614 to ϩ50 mV (holding potential, Ϫ60 mV) (Kwon et al, 2001). It was thus concluded that the relaxant effect of CO on this tissue was not due to inhibition of L-type Ca 2ϩ channels.…”
Section: Carbon Monoxide and Calcium Channelsmentioning
confidence: 92%